Critical perspectives on technology and education - Bulfin, Scott; Johnson, Nicola F., 1976-; Bigum, Chris, 1946- (Palgrave Macmillan's digital education and learning series., 2015)
Critical Perspectives on Technology and Education shows how researchers working in the area of technology and education can use critical perspectives to broaden the "ed-tech" research imagination, opening up new topics, asking new questions, developing theory and articulating an agenda for informed action.